Shared neuroanatomical substrates of impaired phonological working memory across reading disability and autism - Lu, Chunming (Biol Psychiatry Cogn Neurosci Neuroimaging, 2016)
BACKGROUND: Individuals with reading disability or individuals with autism spectrum disorder (ASD) are characterized, respectively, by their difficulties in reading or social communication, but both groups often have impaired phonological working memory (PWM). It is not known whether the impaired PWM reflects distinct or shared neuroanatomical abnormalities in these two diagnostic groups. METHODS: White-matter structural connectivity via diffusion weighted imaging was examined in sixty-four children, ages 5-17 years, with reading disability, ASD, or typical development (TD), who were matched in age, gender, intelligence, and diffusion data quality. RESULTS: Children with reading disability and children with ASD exhibited reduced PWM compared to children with TD. The two diagnostic groups showed altered white-matter microstructure in the temporo-parietal portion of the left arcuate fasciculus (AF) and in the temporo-occipital portion of the right inferior longitudinal fasciculus (ILF), as indexed by reduced fractional anisotropy and increased radial diffusivity. Moreover, the structural integrity of the right ILF was positively correlated with PWM ability in the two diagnostic groups, but not in the TD group. CONCLUSIONS: These findings suggest that impaired PWM is transdiagnostically associated with shared neuroanatomical abnormalities in ASD and reading disability. Microstructural characteristics in left AF and right ILF may play important roles in the development of PWM. The right ILF may support a compensatory mechanism for children with impaired PWM.